2018
DOI: 10.1155/2018/8608327
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and DNA Methylome Dynamics during Triclosan-Induced Cardiomyocyte Differentiation Toxicity

Abstract: Cardiac development is a dynamic process and sensitive to environmental chemicals. Triclosan is widely used as an antibacterial agent and reported to transport across the placenta and affect embryonic development. Here, we used human embryonic stem cell- (hESC-) derived cardiomyocytes (CMs) to determine the effects of TCS exposure on cardiac development. After TCS treatment, the differentiation process was significantly blocked and spontaneous beating rates of CMs were also decreased. Transcriptome analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Their results showed that in the 5735 CpG dinucleotides, 2960 were related to suppressed gene expression, which showed no significant difference with the number of CpGs (2775) whose methylation levels were positively associated with gene expression. Table summarized the relationship between DNA methylation and gene expression . These results indicated that DNA methylation functions as a bidirectional modulator in regulating gene expression, depending on the location of CpG sites, DNA methylation detection method, disease context and specific gene.…”
Section: Discussionmentioning
confidence: 97%
“…Their results showed that in the 5735 CpG dinucleotides, 2960 were related to suppressed gene expression, which showed no significant difference with the number of CpGs (2775) whose methylation levels were positively associated with gene expression. Table summarized the relationship between DNA methylation and gene expression . These results indicated that DNA methylation functions as a bidirectional modulator in regulating gene expression, depending on the location of CpG sites, DNA methylation detection method, disease context and specific gene.…”
Section: Discussionmentioning
confidence: 97%
“…The formation of dental arch depends on the coordinated regulation of a variety of signaling molecules and location signals, which jointly regulate the development process of cell division rate, trend and direction of cell migration, cell differentiation and apoptosis. In the above process, a series of genes and signaling pathways play an important role in regulation, including Sonic hedgehog (Shh) pathway [ 5 ], Wingless-related integration (Wnt) pathway [ 6 ], fibroblast growth factors (FGF) pathway [ 7 ], Transforming growth factor-beta (TGF-β) [ 8 ] pathway and bone morphogenesis proteins (BMPs) family [ 9 11 ]. These signaling molecules bind to corresponding receptors and regulate the expression of specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, exposure to TCS (1 µM) inhibited the differentiation of hESCs into cardiomyocytes and their spontaneous beating. This inhibition occurred through the interference of triclosan with the gene expression (of ACTC1, GATA4, and TNNT2) and with excessive methylations in the DNA [ 81 ].…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%